Hydrodynamic and Geometric Behavior of Two Pericardial Prostheses Implanted in Small Aortic Roots. Issue 1 (January 2018) - Tasca, Giordano; Beniamino Fiore, Gianfranco; Redaelli, Paola; Romagnoni, Claudia; Redaelli, Alberto; Gamba, Amando; Antona, Carlo; Vismara, Riccardo
Abstract : Hydrodynamic performance of stented bioprostheses is far below that of the native valve. One of the reasons is that the internal diameter of the prosthesis is usually smaller than that of the native valve. However, other valve characteristics are also important in generating the pressure drop. We aimed to assess, in an ex vivo pulsatile mock loop, the hydrodynamic behavior of two bioprostheses, Trifecta and Mitroflow, to ascertain which geometric terms are limiting factors in hydrodynamic performance. At stroke volumes between 30 and 60 ml, Trifecta showed lower pressure drop, energy dissipation and valve resistance, and greater effective orifice area. This trend was overturned at higher stroke volumes, with Mitroflow slightly outperforming Trifecta. The geometric determinants were consistent with these results. Trifecta achieved its maximum opening area already at the lowest stroke volumes, featuring a divergent shape at the systolic peak. Mitroflow showed a complex opening pattern, featuring a convergent shape at the systolic peak for lower stroke volumes, while reaching its maximum opening area at higher stroke volumes, with a divergent shape. The two bioprostheses, although similar in design, displayed different biomechanical behaviors. The internal diameter of each bioprosthesis did not show to be strictly correlated with its hydrodynamic characteristics.